Mostrare e dire Sade. Le 120 Giornate di Sodoma di Giuliano Vasilicò - De Santis, Vincenzo (Status Quaestionis, 2022)
“Imperious, passionate, angry, exemplary in everything”: this is how a Dutch periodical comments on Vasilicò’s Sade right after the show in Amsterdam in 1973. Performed for the first time at the Beat 72 theatre in 1972, Vasilicò’s theatrical adaptation of Sade’s novel Les 120 Journées de Sodome is an essential turning point for the “cantine romane”: this show was a sort of initiation that eventually “projected” 1970s Italian avant-garde “on an international stage”. From Bartolucci to Roland Barthes, Vasilicò’s Sade arouses great critical interest, which essentially focuses on the political and philosophical significance of his adaptation, on the performance of the actors, on the scenography and above all on the use of lights. If the relationship between Vasilicò’s play and Sade’s novel has been investigated from the point of view of the construction of the scenes, the relationship with Sade’s language has been less scrutinized by critics. When Vasilicò started working on his play, Italian transla- tions of Sade’s work were in short supply. In addition to the edition introduced by Luigi Bontempelli and in very low circulation, there was the shy version by Adriana Klyngly whi- ch diluted Sade’s lexicon to the limits of censorship. While those translations dilute and dis- simulate, by exposing it through the performance and concentrating it in his script, Vasilicò unveils Sadian aesthetics for the Italian public: starting from the script published in 1973, this research intends to analyse the relationship between Sade’s language and the theatrical language adopted by Vasilicò in his 120 Days, both from a textual and a visual point of view.